Hubungan Model Inquiry Terbimbing (Guided Inquiry Approach) terhadap Keaktifan Belajar PAI Siswa Kelas XI - Rizka Amelia Putri; Indah Muliati (Lembaga Yasin AlSys, 2026)
This study was motivated by the still limited number of investigations examining the relationship between the guided inquiry learning model and students’ learning activeness in Islamic Religious Education and Character Education (Pendidikan Agama Islam dan Budi Pekerti) at the senior high school level, even though low learning activeness has a significant impact on the quality of teaching and learning processes and outcomes. The study aimed to analyze the relationship between the implementation of the guided inquiry learning model and the learning activeness of Grade XI students at SMA Negeri 1 Pariaman. A quantitative approach with a descriptive correlational method was employed, involving 76 Grade XI students selected using a total sampling technique. Data were collected using a guided inquiry learning model questionnaire as variable X and a student learning activeness questionnaire as variable Y, both of which had been tested for validity and reliability. Data were analyzed using descriptive statistics, normality and linearity tests, Product Moment correlation, t-test, and the coefficient of determination. The results showed that the implementation of the guided inquiry learning model was in the “good” category, with an average score of 85.513, and students’ learning activeness was also in the “good” category, with an average score of 87.921. There was a positive and significant relationship between the guided inquiry learning model and students’ learning activeness, with r = 0.500 and p = 0.001 < 0.05, indicating a 25% contribution to learning activeness. These findings are consistent with constructivist learning theory, which emphasizes active student involvement in the learning process, and indicate that the application of guided inquiry plays an important role in enhancing learning activeness. The implications of this study include strengthening the theoretical discourse on the guided inquiry learning model and providing practical recommendations for Islamic Religious Education and Character Education teachers to adopt learning models that foster active student engagement, as well as opening avenues for further research on other factors influencing learning activeness.